Impact of Social Media on Adolescent Social Interaction Patterns in Digital Education - Kafina Agni Fitrati; Rehany Saleha (Journal of Smart Pedagogy and Education, 2025)
This research analyzes the impact of social media on adolescent social interaction patterns within Indonesia’s digital education landscape. Utilizing a qualitative systematic literature review guided by Media Ecology and Social Capital theories, the study examines how platforms like TikTok and Instagram reshape social dynamics. Findings indicate that while digital connectivity expands bridging social capital through diverse global networks, it simultaneously erodes bonding capital and face-to-face communication quality. The emergence of a pervasive "scroll culture" and "phubbing" behaviors in schools has led to a significant decline in interpersonal empathy and academic focus. Furthermore, psychosocial risks such as FOMO and cyberbullying underscore a "digital native paradox," where technical proficiency lacks corresponding ethical literacy. The study concludes that mitigating these negative impacts requires a robust multi-sectoral framework, integrating digital literacy, parental and educator collaboration, and strategic regulatory interventions. Fostering a balanced media ecology is essential to ensure healthy adolescent development in mediated systems.